Antimicrobial susceptibility and impact of macrolide antibiotics onMoraxella catarrhalisin the upper and lower airways of children with chronic endobronchial suppuration. Issue 8 (August 2019) - Hare, Kim M.; Seib, Kate L.; Chang, Anne B.; Harris, Tegan M.; Spargo, Jessie C.; Smith‐Vaughan, Heidi C.
Abstract : Introduction. : Moraxella catarrhalis is an important but insufficiently studied respiratory pathogen. Aim. : To determine antibiotic susceptibility and impact of recent antibiotics on M. catarrhalis from children with chronic endobronchial suppuration. Methodology. : We cultured nasopharyngeal (NP) swabs and bronchoalveolar lavage (BAL) fluids collected from children who were prospectively enrolled in studies of chronic cough and had flexible bronchoscopy performed. Recent β ‐lactam or macrolide antibiotic use was recorded. M. catarrhalis isolates stored at −80 °C were re‐cultured and susceptibility determined to a range of antibiotics including the macrolide antibiotic erythromycin. Results. : Data from concurrently collected NP and BAL specimens were available from 547 children (median age 2.4 years) enrolled from 2007 to 2016. M. catarrhalis NP carriage was detected in 149 (27 %) children and lower airway infection (≥10 4 c.f.u. ml −1 BAL) in 67 (12 %) children. In total, 91 % of 222 M . catarrhalis isolates were β ‐lactamase producers, and non‐susceptibility was high to benzylpenicillin (98 %), cefaclor (39 %) and cotrimoxazole (38 %). Overall, >97 % isolates were susceptible to cefuroxime, chloramphenicol, erythromycin and tetracycline; three isolates were erythromycin‐resistant (MIC >0.5 mg l −1 ). Recent macrolide antibiotics ( n =152 children, 28 %) were associated with significantly reduced M. catarrhalis carriage and lower airway infection episodes compared to children who did not receive macrolides; odds ratios 0.19 (95 % CI 0.10‐0.35) and 0.15 (0.04‐0.41), respectively. Conclusion. : Despite the frequent use of macrolides, few macrolide‐resistant isolates were detected. This suggests a fitness cost associated with macrolide resistance in M. catarrhalis . Macrolide antibiotics remain an effective choice for treating M. catarrhalis lower airway infection in children with chronic endobronchial suppuration.